The kinematics of upper extremity reaching: a reliability study on people with and without shoulder impingement syndrome - Roy Jean-Sébastien; Moffet Hélène; McFadyen Bradford J; MacDermid Joy C (BMC, 2010)
Abstract Background Tasks chosen to evaluate motor performance should reflect the movement deficits characteristic of the target population and present an appropriate challenge for the patients who would be evaluated. A reaching task that evaluates impairment characteristics of people with shoulder impingement syndrome (SIS) was developed to evaluate the motor performance of this population. The objectives of this study were to characterize the reproducibility of this reaching task in people with and without SIS and to evaluate the impact of the number of trials on reproducibility. Methods Thirty subjects with SIS and twenty healthy subjects participated in the first measurement session to evaluate intrasession reliability. Ten healthy subjects were retested within 2 to 7 days to assess intersession reliability. At each measurement session, upper extremity kinematic patterns were evaluated during a reaching task. Ten trials were recorded. Thereafter, the upper extremity position at the end of reaching and total joint excursion that occurred during reaching were calculated. Intraclass correlation coefficient (ICC) and minimal detectable change (MDC) were used to estimate intra and intersession reliability. Results Intrasession reliability for total joint excursion was good to very good when based on the first two trials (0.77<ICC<0.99), and very good when based on either the first or last five trials (ICC>0.92). As for end-reach position, intrasession reliability was very good when using either the first two, first five or last five trials (ICC>0.82). Globally, MDC were smaller for the last five trials. Intersession reliability of total joint excursion and position at the end of reaching was good to very good when using the mean of the first two or five trials (0.69<ICC<0.95), and very good when using the mean of the ten trials (ICC>0.82). For most joints, MDC were smaller when using all ten trials. Conclusions The reaching task proposed to evaluate the upper limb motor performance was found reliable in people with and without SIS. Furthermore, the minimal difference necessary to infer a meaningful change in motor performance was determined, indicating that relatively small changes in task performance can be interpreted as a change in motor performance.